组合式气动柔性手指 (2023)
本发明解决的技术问题是提供了一种组合式气动柔性手指。在模具中真空浇注成型硅胶手指块，用液态硅胶粘接好分支气管、连通气管和硅胶手指块，形成硅胶手指段。将各硅胶手指段自由组合，调整安装角度，装配好，用扎带扎紧。选择性封堵各硅胶手指段的分支气管或连通气管，经相应的分支气管或连通气管通入压缩气体，可自由控制各段硅胶手指段的变形弯曲，完成各种不同的动作。本发明能最大限制的满足各种使用条件和要求，其软体特征特别适用于传统机械手不宜使用的脆性目标等对象。 The invention provides a combined type pneumatic flexible finger. Silicon finger blocks are subject to vacuum pouring and molding in a mold, branch air pipes, communication air pipes and the silicon finger blocks are bonded through liquid-state silica gel, and silicon finger segments are formed; the silicon finger segments are freely combined, the mounting angle is adjusted, and after assembling is carried out, the segments are tightened through ribbons; the branch air pipes or communication air pipes of the silicon finger segments are selectively blocked, compressed air is led in through the corresponding branch air pipes or communication air pipes, deformation bending of the silicon finger blocks can be freely controlled, and various different actions are completed; and according to the c